Organizational structure of a state agency: concept, typology and directions of application to the system of the National Police of Ukraine - K. L. Buhaichuk (Bulletin of Kharkiv National University of Internal Affairs)
The author of the paper has analyzed the general theoretical approaches to determining the content and characteristics of the organizational structures of state agencies; has formulated the key principles for the formation of organizational structures. Based on the research of scientific works on the theory of public administration, administrative law, management, public management, the author has formulated own definition of the concept of “organizational structure of the National Police of Ukraine”.